BIPOLAR TRANSURETHRAL RESECTION OF THE PROSTATE – THE MODERN APPROACH (REVUE ROUMAINE DES SCIENCES TECHNIQUES — SÉRIE ÉLECTROTECHNIQUE ET ÉNERGÉTIQUE, 2021)
Benign prostatic hyperplasia (BPH) is a common condition of the aging male, affecting a significant percentage of the population. The last decades were marked by a continuous evolution of the surgical treatment for BPH, with newer technologies promising less invasive approaches, better outcomes, and fewer complications. Bipolar transurethral resection (B-TURP) is the latest development in the field and it already proved its superiority over its predecessors. Our paper aims to review the technology behind this surgical technique, its main advantages, and the limits of the method. We highlight the indications, main complications, and results of this surgical technique while comparing the data with the “classical” TURP. We conclude that the advances made by technology bring a real benefit both for the patients and medical professionals involved in the treatment of BPH.